2011
DOI: 10.2147/vhrm.s14356
|View full text |Cite
|
Sign up to set email alerts
|

Critical update for the clinical use of L-carnitine analogs in cardiometabolic disorders

Abstract: Acetyl-L-carnitine (ALC) and propionyl-L-carnitine (PLC) are two naturally occurring carnitine derivates formed by carnitine acetyltransferase. The beneficial cardiovascular effects of ALC and PLC have been extensively evaluated in animals and humans during the last 20 years. For instance, many clinical trials have suggested ALC and PLC as potential strategies in the management of peripheral arterial disease, heart and cerebral ischemia, and congestive heart failure. As a result, several experts have already a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 69 publications
0
17
0
1
Order By: Relevance
“…The acylcarnitines themselves are seemingly attractive candidates; however, the weight of evidence at this stage suggests that these metabolites function in a homeostatic capacity to relieve mitochondrial stress (Figure 1) (Muoio et al, (in press), Mingorance et al, 2011; Noland et al, 2009; Power et al, 2007). Another hypothesis that has gained momentum in recent years centers on the premise that mitochondrial-derived ROS modulate insulin signaling (Bloch-Damti and Bashan, 2005; Evans et al, 2005).…”
Section: Mitochondrial Stress: a Contemporary View Of The Randle Cyclementioning
confidence: 99%
“…The acylcarnitines themselves are seemingly attractive candidates; however, the weight of evidence at this stage suggests that these metabolites function in a homeostatic capacity to relieve mitochondrial stress (Figure 1) (Muoio et al, (in press), Mingorance et al, 2011; Noland et al, 2009; Power et al, 2007). Another hypothesis that has gained momentum in recent years centers on the premise that mitochondrial-derived ROS modulate insulin signaling (Bloch-Damti and Bashan, 2005; Evans et al, 2005).…”
Section: Mitochondrial Stress: a Contemporary View Of The Randle Cyclementioning
confidence: 99%
“…Many clinical trials have suggested acetyl-L-carnitine (ALC) and propionyl-L-carnitine (PLC), two naturally occurring carnitine derivates, as potential strategies in the management of peripheral arterial disease (PAD), heart and cerebral ischemia, and congestive heart failure [35]. The beneficial effects of PLC on PAD, particularly in alleviating intermittent claudication, have been widely studied.…”
Section: Cam Effects On the Cardiovascular System And Cvd Risk Facmentioning
confidence: 99%
“…The beneficial effects of PLC on PAD, particularly in alleviating intermittent claudication, have been widely studied. It is generally agreed upon that PLC is able to improve exercise tolerance in terms of increasing the maximum walking distance in patients suffering from intermittent claudication as well as to improve most measures of quality of life (overall physical activity, pain while walking, and psychological activity) [35]. The recent Trans-Atlantic Inter-Society Consensus II update recommends the use of PLC in combination with physical training to improve the symptoms associated with PAD [35].…”
Section: Cam Effects On the Cardiovascular System And Cvd Risk Facmentioning
confidence: 99%
See 1 more Smart Citation
“…Carnitine derivatives are potent antiradical agents and may protect tissues from oxidative damage [10], [11]. Acetyl-L-carnitine (ALC) (a carnitine derivative) possesses similar physiological functions but better bioavailability and antioxidant capacity compared with carnitine [12].…”
Section: Introductionmentioning
confidence: 99%